Identification of Learning Problems in Physical Education Sports and Health Subject during the Covid-19 Pandemic - Mu’arifin Mu’arifin; Mashud Mashud; Pinton Setya Mustafa (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
The Covid-19 pandemic has been a challenge primarily for sports physical education and health learning (SPEH) since it needs to be provided using face-to-face to obtain the learning process in the demonstration, observation, evaluation, and improvement in learning motion. Therefore, this study aims to determine the learning conditions of SPEH during the Covid-19 pandemic. This study involved a descriptive quantitative method through questionnaire provided to the respondents involved in this research. The schools involved as samples are 150 SPEH Teachers in the elementary, junior, and high school levels in East Java of Indonesia. The findings indicate that several obstacles during the pandemic are insufficient infrastructure and the ability of teachers and students to implement SPEH learning, implication of this research is to provide an overview of SPEH learning patterns during the Covid-19 pandemic. This study concludes that there is a remarkable impact of the Covid-19 pandemic on SPEH learning, which suggests that in providing learning online, problems such as delivering practical material cannot be controlled properly in implementing online learning.